CSR AND PURCHASE INTENTIONS (A STUDY OF CENTRAL JAVA EARTHQUAKE) - Kresno Agus Hendarto (Universitas Hayam Wuruk Perbanas, 2012)
In Indonesia, the debate on CSR concerning its implementation to be obligatory or not is stillgoing on even though the Constitution Court had decided, on April 2009, requesting that itshould be reviewed, especially the article 74 of the Laws no 40, 2007, that regulates suchmatter. This study is aimed to analyze the belief, attitude, and intention to purchase the productsfrom the companies that have implemented CSR. The analysis was conducted in the regenciesof Bantul, Sleman, Klaten, and Jogjakarta which exactly on May 27, 2006, these regionswere affected by the earthquake. This study was done by combining both qualitativeand quantitative methods. In the first phase, the data were collected by means of focusedgroup discussion in the radio of RRI program 1 Jogjakarta. After this, the data were analyzedqualitatively. The results of this were used as the basis to to a survey on 100 consumers.This was analyzed using partial least square. It showed that the consumers have awarenesstowards CRS that was implemented by the companies, and therefore, they mediated theirrelationship by showing their belief and intention to purchase the products.